The excellent mind: intellectual virtues for everyday life - King, Nathan L. (Oxford scholarship online, 2021)
Nathan L. King's 'The Excellent Mind' considers the importance of the intellectual virtues: the character traits of excellent thinkers. He explains what it means to have an excellent mind: one that is curious, careful, self-reliant, humble, honest, persevering, courageous, open, firm, and wise. He shows how the intellectual virtues are critical to living everyday life. They are deeply intertwined with moral virtues, and our intellectual character guides our actions and beliefs. The book is thoroughly accessible and designed for students, not just in philosophy and critical thinking classes, but across the curriculum.